Calcific constrictive pericarditis due to rheumatoid arthritis. Issue 771 (January 1990) - Manji, H.; Raven, P.
Abstract : A patient with calcific constrictive pericarditis due to rheumatoid arthritis is presented: the literature reveals only one previous case which was attributed to the long duration of the rheumatoid arthritis.